Efektivitas Program Layanan Bimbingan Klasikal untuk Mengembangkan Empati pada Mahasiswa - Cahyati, Siti; Rachmaniar, Ananda; Rayaginansih, Syari Fitrah (Jurnal Dimamu, 2025)
In the view of social professions such as counseling and psychotherapy, empathy plays an important role as a bridge to build an effective therapeutic relationship so that the counselor can understand the client's experience, a low level of empathy will clearly indicate a destructive nature of the relationship between the client and the counselor. The purpose of this study is to determine the effectiveness of classical guidance services in developing empathy for students of the guidance and counseling study program at Ma'soem University class of 2023. A quantitative method with a type of pre-experimental research of one group pre-test post-test design was used in this study, the population of 42 students with the use of saturated samples. The measuring tool used is the Empathy Scale for Prospective Counselor (ESPC) which was developed based on Segal's theory (2018). The results showed that the significance value of 0.875 and the Tcount value of -158 showed that there was no difference between the pre-test score and the post-test score, meaning that classical guidance services were not effective in developing empathy, Thus, in this study, H0 was accepted and H1 was rejected.